TOWARD A COMPREHENSIVE DEFINITION OF THE NON-USER. (May 2020) - Augustin, L.; Kokoschko, B.; Wiesner, M.; Schabacker, M.
Abstract: The user has been very well defined over the last decades. With human-centered design becoming more widely applied within various industries, the user's needs are being taken into account more than ever. What is often overlooked is the user's counterpart: the non-user. Integrating the non-user into modern development projects provides great additional value. This paper is compiling current definitions in order to analyse them within the context of product development and to make a contribution toward a comprehensive definition of the non-user that can be applied to various disciplines.